PENERAPAN TEKNOLOGI TEPAT GUNAALAT SIRAT (SPLIT DAN IRAT) SEBAGAI UPAYA PEMERDAYAAN PENGRAJIN BAMBU DI DESA KAYUBIHI - I G N Arya Bayu Kartika; D N Agung Nareswara Natha; I Kadek Deni Saputra; Gusti Ngurah Janardana (Jurnal SPEKTRUM, 2025)
Kayubihi Village, Bangli District, Bali, has great potential in the bamboo craft industry because 15% of its population works as craftsmen. However, limited traditional tools lead to low productivity and low quality results. This study aims to analyze the effectiveness of the use of the SIRAT (Split and Irat) tool in increasing the efficiency and productivity of craftsmen. The research method used is descriptive quantitative through structured observation and questionnaires. The results showed that the SIRAT tool can reduce processing time, from 35 seconds to 2 seconds in the split process, and from 73 seconds to 50 seconds in the irat process. Average split production increased from 0.57–1.42 stems per day to 1.85–3.42 stems, while irat production increased from 50.29–125.71 stems to 163.43–301.71 stems per day, or equivalent to an increase of 130%–225%. In addition, this tool produces more uniform bamboo sizes, reduces labor load, and reduces the risk of work accidents. Thus, the application of the SIRAT tool has proven effective in increasing productivity and quality of results, while also supporting Kayubihi Village as a bamboo craft center.